2009
DOI: 10.1007/s11240-009-9648-1
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of embryogenic cell suspensions of taro (Colocasia esculenta var. esculenta) and plant regeneration

Abstract: Embryogenic callus was initiated by culturing in vitro taro corm slices on agar-solidified half-strength MS medium containing 2.0 mg/L 2,4-dichlorophenoxyacetic acid (2,4-D) for 20 days followed by transfer to 1.0 mg/L thidiazuron (TDZ). Callus was subsequently proliferated on solid medium containing 1.0 mg/L TDZ, 0.5 mg/L 2,4-D and 800 mg/L glutamine before transfer to liquid medium containing the same components but with reduced glutamine (100 mg/L). After 3 months in liquid culture on an orbital shaker, cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 18 publications
2
11
0
2
Order By: Relevance
“…We have previously shown that AGPs are released in the culture medium of embryogenic and non-embryogenic chicories but no major difference in the soluble AGP profiles was detected. 33,38 We have also shown earlier that complexation of soluble AGPs with b-D Glc Yariv reagent inhibits mitosis while cell reactivation still occurs. 33,38 To test whether the difference in the ISE of the embryogenic hybrid and of the cv Pévèle was correlated with differences in the quantity of released AGPs, we determined the mean quantity of soluble AGPs Figure 1.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…We have previously shown that AGPs are released in the culture medium of embryogenic and non-embryogenic chicories but no major difference in the soluble AGP profiles was detected. 33,38 We have also shown earlier that complexation of soluble AGPs with b-D Glc Yariv reagent inhibits mitosis while cell reactivation still occurs. 33,38 To test whether the difference in the ISE of the embryogenic hybrid and of the cv Pévèle was correlated with differences in the quantity of released AGPs, we determined the mean quantity of soluble AGPs Figure 1.…”
Section: Resultsmentioning
confidence: 73%
“…33,38 We have also shown earlier that complexation of soluble AGPs with b-D Glc Yariv reagent inhibits mitosis while cell reactivation still occurs. 33,38 To test whether the difference in the ISE of the embryogenic hybrid and of the cv Pévèle was correlated with differences in the quantity of released AGPs, we determined the mean quantity of soluble AGPs Figure 1. Effects of pretreatment of leaves of the embryogenic hybrid of Cichorium, with 0.5 mM polyamines (putrescine, spermidine, or spermine), of 330 mM glycerol,or of several concentrations of (± ) cis, trans abscisic acid (ABA), on the number of somatic embryos (mean ± SEM for n = 9 independent experiments).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Means in each column followed by different letters are significantly different according to DMRT at P<0.05 1997) and enhances the synthesis of certain metabolites (Deo et al 2010). Earlier, the beneficial role of Lglutamine in the induction of somatic embryogenesis has also been reported in a number of studies (Garin et al 2000;Robichaud et al 2004;Zouine and Hadrami 2007;Deo et al 2010).…”
Section: Effect Of Amino Acids On the Induction Of Somatic Embryogenesismentioning
confidence: 87%
“…Means in each column followed by different letters are significantly different according to DMRT at P<0.05 1997) and enhances the synthesis of certain metabolites (Deo et al 2010). Earlier, the beneficial role of Lglutamine in the induction of somatic embryogenesis has also been reported in a number of studies (Garin et al 2000;Robichaud et al 2004;Zouine and Hadrami 2007;Deo et al 2010). In contrast to our observations, insignificant role of L-glutamine in somatic embryogenesis was also reported in Acacia catechu (Rout et al 1995), Prunus incise (Cheong and Pooler 2004), Psidium guajava (Rai et al 2009).…”
Section: Effect Of Amino Acids On the Induction Of Somatic Embryogenesismentioning
confidence: 97%